2017
DOI: 10.1093/cercor/bhx261
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic Modulation of a Minor Fraction of Parvalbumin-Positive Interneurons Specifically Affects Spatiotemporal Dynamics of Spontaneous and Sensory-Evoked Activity in Mouse Somatosensory Cortex in Vivo

Abstract: Parvalbumin (PV) positive interneurons exert strong effects on the neocortical excitatory network, but it remains unclear how they impact the spatiotemporal dynamics of sensory processing in the somatosensory cortex. Here, we characterized the effects of optogenetic inhibition and activation of PV interneurons on spontaneous and sensory-evoked activity in mouse barrel cortex in vivo. Inhibiting PV interneurons led to a broad-spectrum power increase both in spontaneous and sensory-evoked activity. Whisker-evoke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 64 publications
(111 reference statements)
8
35
0
Order By: Relevance
“…We found strong and dense co-expression across targeted cortical layers II/III and V/VI. Note, that layer IV seems to be difficult to target with AAVs of serotype I/II, as reported previously [28,29].…”
Section: Careful Titration Of Viral Vectors Is Needed To Achieve Strosupporting
confidence: 65%
“…We found strong and dense co-expression across targeted cortical layers II/III and V/VI. Note, that layer IV seems to be difficult to target with AAVs of serotype I/II, as reported previously [28,29].…”
Section: Careful Titration Of Viral Vectors Is Needed To Achieve Strosupporting
confidence: 65%
“…Our hypothesis that recurrent and lateral inhibition might be mediated by PV+ interneurons is supported by a recent study showing that optogenetic inhibition of PV+ neurons causes an increase in lateral excitation, whereas optogenetic activation causes a strong reduction (Yang et al . ). In addition, activation of PV+ interneurons is most efficient within a 20 ms window to reduce the responses of the principal barrel.…”
Section: Discussionmentioning
confidence: 97%
“…For example, Zhu et al 13 showed that suppressing PV-neurons is sufficient to increase responses to visual stimuli and improves SNR. Manipulating PV neuron activity also alters the spontaneous activity level in the excitatory neurons 13,14,24,[53][54][55][56][57][58][59][60][61][62] . Our recent study showed that deficit in gap detection associated with noise exposure-induced tinnitus is mostly mediated by reduction in PV-but not SOM-neurons, and activation of PV-neurons using DREADD can partially ameliorate this deficit 63 .…”
Section: Enhanced Inhibition On Evoked and Spontaneous Activities M-mentioning
confidence: 99%